Nutrient Distribution in East Antarctic Summer Sea Ice: A Potential Iron Contribution From Glacial Basal Melt. Issue 12 (27th November 2020) - Duprat, L.; Corkill, M.; Genovese, C.; Townsend, A. T.; Moreau, S.; Meiners, K. M.; Lannuzel, D.
Abstract: Antarctic sea ice can incorporate high levels of iron (Fe) during its formation and has been suggested as an important source of this essential micronutrient to Southern Ocean surface waters during the melt season. Over the last decade, a limited number of studies have quantified the Fe pool in Antarctic sea ice, with a focus on late winter and spring. Here we study the distribution of operationally defined dissolved and particulate Fe from nine sites sampled between Wilkes Land and King George V Land during austral summer 2016/2017. Results point toward a net heterotrophic sea‐ice community, consistent with the observed nitrate limitation (<1 μM). We postulate that the recycling of the high particulate Fe pool in summer sea ice supplies sufficient (∼3 nM) levels of dissolved Fe to sustain ice algal growth. The remineralization of particulate Fe is likely favored by high concentrations of exopolysaccharides (113–16, 290 μg xeq L −1 ) which can serve as a hotspot for bacterial activity. Finally, results indicate a potential relationship between glacial meltwater discharged from the Moscow University Ice Shelf and the occurrence of Fe‐rich (∼4.3 μM) platelet ice in its vicinity. As climate change is expected to result in enhanced Fe‐rich glacial discharge and changes in summer sea‐ice extent and quality, the processes influencing Fe distribution in sea ice that persists into summer need to be better constrained. Plain Language Summary: Iron (Fe) plays a crucial role in microalgal physiology and can control their growth in the Southern Ocean, where Fe concentrations are naturally low. Antarctic sea ice can incorporate high levels of Fe during its formation triggering phytoplankton blooms at the sea‐ice edge during the melt season. No studies to date have assessed sea‐ice Fe distributions in East Antarctica during mid‐ to late summer. Here we discuss Fe distribution in parallel with key sea‐ice physical and biological parameters measured during an expedition to East Antarctica in summer 2016/2017 to answer our central question: is Fe limiting sea‐ice primary productivity during summer? Results suggest nitrate, rather than Fe is the key nutrient controlling sea‐ice algal growth at this time of the year. We also found Fe‐rich platelet ice incorporated underneath pack ice sampled near the Moscow University Ice Shelf which suggests the potential accretion of Fe‐rich ice shelf waters under the sea ice. As climate change is expected to accelerate Antarctic ice shelve melting, a better understanding of how increased rates of glacial meltwater discharge will impact the distribution of Fe within the sea ice during summer is needed. Key Points: Primary production in East Antarctic fast and pack sea ice is not Fe‐limited during summer Low nitrate and high exopolysaccharide concentrations suggest heterotrophic dominance in Antarctic summer sea ice Fe‐rich platelet sea ice near the Moscow University Ice Shelf indicates an influence of glacial meltwater in the coastal distribution of Fe